2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487446
|View full text |Cite
|
Sign up to set email alerts
|

Task frame estimation during model-based teleoperation for satellite servicing

Abstract: Model-based teleoperation is suitable for systems with large communication delay because the operator interacts with a model of the task while the remote robot uses sensorbased control to replicate that interaction on the physical system. When the model geometry is accurately known, it is only necessary to register it to the remote physical system. If registration errors can be detected during the task, it is possible to update the local task frame (as in model mediated teleoperation) or the remote task frame.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The authors propose a robotic control architecture that helps a human operator in handling long objects by imposing virtual nonholonomic constraints. More recently, Li and Kazanzides [21] proposed a shared-control architecture for cutting in satellite servicing scenarios under time delay. The task consisted of cutting a straight line in multi-layer insulation (MLI) blankets (a thermal insulation patch used to cover satellites).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors propose a robotic control architecture that helps a human operator in handling long objects by imposing virtual nonholonomic constraints. More recently, Li and Kazanzides [21] proposed a shared-control architecture for cutting in satellite servicing scenarios under time delay. The task consisted of cutting a straight line in multi-layer insulation (MLI) blankets (a thermal insulation patch used to cover satellites).…”
Section: Introductionmentioning
confidence: 99%
“…While the approaches of [22] and [21] are promising, they mainly focus on treating the time delay in the system rather than the cutting task itself. In fact, they all consider rather simple cutting tasks (straight lines).…”
Section: Introductionmentioning
confidence: 99%
“…First, we developed a method to enable an operator to more accurately align the virtual plane by dynamically texturing the virtual plane with the purpose of adding visual distortion until the virtual plane is accurately aligned with the real plane, Leonard (2015) . Then, Li and Kazanzides (2016) reported the development of a method to update the orientation of the virtual plane based on sensor feedback during the task, as described in Section 2.5 .…”
Section: Methodsmentioning
confidence: 99%
“…In Section 2.4.1 , we observed that in the directions of position/velocity control, the measured force could be used to monitor the task performance. Here, we consider that in directions of force control, the measured position can be used to update the task model, Li and Kazanzides (2016) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation